Reformas necesarias al código de comercio respecto de la ley que regula la venta con reserva de dominio. - Pazos Villacís, Alex David (2013)
The sale with reservation of ownership is treated in our country in the Commercial Code as a title section that talks about the sale, with a special procedure to follow when there is default. The Commercial Code Article 1 of the section on sale with reservation of title, notes that sales of personal property to be made in installments, the seller may retain the domain of the objects sold until the buyer has paid the full price, therefore the buyer will acquire the ownership of the thing with the payment of the full price, but bear the risk of the same from the time that the seller receives power. This special procedure, which should be uniform in the practical treatment by judges has become an area of conflict because of the lack of uniformity to the application of legal rules laid down in legislation and legal standards is provided in the Act is the sale subject domain, it becomes problematic due to its size which allows excessive interpretation by judges to examine the causes. The fundamental problem is that many times the same treatment is given to articles that indicate the procedure to be followed in the apprehension , which entitles the buyer to recover the fine if within fifteen days after the due date is updated in the payment of fees or provides sufficient security to the satisfaction of the seller, provided that this has not been declared defeated all liability early - to articles that indicate the procedure to follow when the seller has chosen to direct the closing of the asset in accordance with the procedure set forth to the closing of the commercial pledge . In this sense, both in Article 9 and Article 10, it must specify each of the methods according to the option you go the creditor , avoiding in this way, violate the rights of both the creditor and the debtor at the execution time of booking and in the release of the rather reserved .